Markers for DNA damage are induced in the rat colon by the Alternaria toxin altertoxin-II, but not a complex extract of cultured Alternaria alternata - Aichinger, Georg; Pahlke, Gudrun; Puntscher, Hannes; Groestlinger, Julia; Grabher, Stephanie; Braun, Dominik; Tillmann, Katharina; Plasenzotti, Roberto; Del Favero, Giorgia; Warth, Benedikt; Höger, Harald; Marko, Doris (Frontiers in Toxicology, 2022)
Mycotoxins produced by Alternaria spp. act genotoxic in cell-based studies, but data on their toxicity in vivo is scarce and urgently required for risk assessment. Thus, male Sprague-Dawley rats received single doses of a complex Alternaria toxin extract (CE; 50 mg/kg bw), altertoxin II (ATX-II; 0.21 mg/kg bw) or vehicle by gavage, one of the most genotoxic metabolites in vitro and were sacrificed after 3 or 24 h, respectively. Using SDS-PAGE/Western Blot, a significant increase of histone 2a.X phosphorylation and depletion of the native protein was observed for rats that were exposed to ATX-II for 24 h. Applying RT-PCR array technology we identified genes of interest for qRT-PCR testing, which in turn confirmed an induction of Rnf8 transcription in the colon of rats treated with ATX-II for 3 h and CE for 24 h. A decrease of Cdkn1a transcription was observed in rats exposed to ATX-II for 24 h, possibly indicating tissue repair after chemical injury. In contrast to the observed response in the colon, no markers for genotoxicity were induced in the liver of treated animals. We hereby provide the first report of ATX-II as a genotoxicant in vivo. Deviating results for similar concentrations of ATX-II in a natural Alternaria toxin mixture argue for substantial mixture effects.